A 48-month clinical performance of hybrid ceramic fragment restorations manufactured in CAD/CAM in non-carious cervical lesions: case report - Michael Willian Favoreto; Gabriel David Cochinski; Eveline Claudia Martini; Thalita de Paris Matos; Matheus Coelho Bandeca; Alessandro Dourado Loguercio (Restorative Dentistry & Endodontics)
From the restorative perspective, various methods are available to prevent the progression of non-carious cervical lesions. Direct, semi-direct, and indirect composite resin techniques and indirect ceramic restorations are commonly recommended. In this context, semi-direct and indirect restoration approaches are increasingly favored, particularly as digital dentistry becomes more prevalent. To illustrate this, we present a case report demonstrating the efficacy of hybrid ceramic fragments fabricated using computer-aided design (CAD)/computer-aided manufacturing (CAM) technology and cemented with resin cement in treating non-carious cervical lesions over a 48-month follow-up period. A 24-year-old male patient sought treatment for aesthetic concerns and dentin hypersensitivity in the cervical region of the lower premolar teeth. Clinical examination confirmed the presence of two non-carious cervical lesions in the buccal region of teeth #44 and #45. The treatment plan involved indirect restoration using CAD/CAM-fabricated hybrid ceramic fragments as a restorative material. After 48 months, the hybrid ceramic material exhibited excellent adaptation and durability provided by the CAD/CAM system. This case underscores the effectiveness of hybrid ceramic fragments in restoring non-carious cervical lesions, highlighting their long-term stability and clinical success.